(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This study about inequality(s) occupies a relevant space in therecentacademic contributions from looks that suppose to privilege generally omitted categories, overcoming a traditional area that prioritizes income inequalities. The urban space is also analyzed in the (re) production of the social inequality in the Latin-American cities (Segura, 2014). The predominance of the inequality in the center-periphery scheme of metropolitan structure reinforces the model of city that does not manage to conquer the invisible barriers placed daily in the life of the population (Caldeira, 2000). Such barriers are remeasured from the complexity of the metropolis producing inequalities on multiple scales. This work is part of an investigation on public policies of habitat from emergent approaches. In previous instances we approach gender constructions in the speeches and practices of the habitat policies implemented in Tucumán in the 2004-2008. Between 2007 and 2015 a series of institutional, legislative and legal changes took place in Argentina with the aim expandingrights and social and gender equality. These must be considered to think today challenges in the equity agendas. From the disciplinary perspective of urbanism, the 21st century finds us with problems and challenges raised global level regarding inclusion in cities. From research instances and collective reflection processes on Latin American metropolises, similar dynamics linked to metropolitan expansion, inequality and vulnerability are evident in the 2005-2015 period. Both lines research, the one that links politics and gender and the one related to the metropolitan agenda and rights, dialogue in this article. Some questions that guide the work refer to: what implies thinking today and in our context, in more inclusive and democratic cities? Which are the advances and challenges of the public policies developed in the last decade? What gender inequalities come together in metropolitan spaces? What answers does the urban agenda demand? This paper presents some reflections on how gender inequalities are expressed in the metropolitan area of Tucumán and on the level of responses, the challenges of the urban and metropolitan agenda regarding the incorporation of human rights and gender equality.